Literature Review: Perceptions of Active Smokers on Health Promotion Media - Sendy Martha Mareta; Lina Handayani (PLACENTUM: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2021)
Background: At a vulnerable age they continue to smoke, if they do not apply PHBS (Healthy and Clean Living Behavior), the degree of health in the elderly will decrease and the diseases caused by cigarettes will increase. To overcome this, health promotion is needed to increase elderly knowledge of the negative impact of cigarettes, substances contained in cigarettes, and change the mindset of the elderly about cigarettes.Destination: The purpose of this review literature is to analyze various perceptions of elderly active smokers about health promotion media.Method: This study used the method is literature review. The method used in searching research journal articles is  google scholar and garuda database. Keywords which used are “Media promkes”, “Precepts Active Smokers” and “Promkes”. We found 15 research journal articles with the year published from 2016 to 2021. At the time of the search process the research journal article authors found 21 research journal articles. Filtering is based on the suitability of topics, research methods, and the results of each journal article research.Results: Most indonesian people when looking at health promotion media in the form of images warning of the dangers of smoking arise various perceptions. As they perceived the image was just an engineering one, they perceived that the image was disgusting and frightening, and the picture warning of the dangers of smoking was not large enough.Conclusion: Electronic health promotion media such as, video on the dangers of smoking, short films on the dangers of smoking, true stories of former people with throat cancer, etc. are more effective than visual health promotion media in suppressing the percentage of smokers in Indonesia